2017
DOI: 10.17660/actahortic.2017.1173.58
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different drying methods on phenolic content, antioxidant capacity and general characteristics of selected dark colored Turkish fig cultivars

Abstract: Fig fruit is a good source of minerals and crude fibers. The dark-colored fig cultivars rich in anthocyanins are also known with their high polyphenol content. However, although there are many different dark-colored fig cultivars grown in Turkey, the dried fig industry has traditionally been concentrated on drying of several yellow-colored fig cultivars. The aim of this study is to determine the effects of sundrying and oven-drying on some general characteristics, phenolic content and antioxidant capacity of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
(7 reference statements)
3
6
0
Order By: Relevance
“…In addition, dark-colored peels exhibited the highest antioxidant capacity compared to the light-colored ones. These results were similar to those reported by Solomon et al [ 29 ], Pande and Akoh, Ammar et al, Konak et al [ 35 , 36 , 37 ], where several methodologies have been employed to assess the in vitro antioxidant capacity of different fig parts. It is noteworthy that such in vitro antioxidant assays are semi-quantitative and do not always represent the in vivo antioxidant capacity [ 38 ].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, dark-colored peels exhibited the highest antioxidant capacity compared to the light-colored ones. These results were similar to those reported by Solomon et al [ 29 ], Pande and Akoh, Ammar et al, Konak et al [ 35 , 36 , 37 ], where several methodologies have been employed to assess the in vitro antioxidant capacity of different fig parts. It is noteworthy that such in vitro antioxidant assays are semi-quantitative and do not always represent the in vivo antioxidant capacity [ 38 ].…”
Section: Resultssupporting
confidence: 91%
“…It combined the highest levels of flavonoids compounds and consequently showed high level of DPPH• and ABTS•+ radical scavenging capacity. This cultivar has dark-colored fruits, which is in accordance with several studies, which showed that fig skins have much higher amounts of phytochemical compounds, mainly flavonoids, which strongly contribute to the antioxidant capacity [18,29,30,35,37].…”
Section: Heat Map Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…As a result, figs from dark‐colored cultivars had an antioxidant potential of 3–4 times greater than those from light‐colored cultivars. These results were supported by numerous research findings (Faleh et al., 2012; Konak et al., 2015; Pereira et al., 2020). The sun‐drying process positively impacted antioxidant potential, enhancing the antioxidant activities of dried figs compared to fresh ones, according to the impact of drying on antioxidant capacity (Chang et al., 2016; Paramanya et al., 2023).…”
Section: Health Benefits Of Ficus Carica Ingredients and Bioactive Co...supporting
confidence: 85%
“…While TP values of 'Bursa Siyahı', 'Sarı Zeybek' and 'Yeşilgüz' accessions in the study by Çalışkan et al [2012] were 118.4, 76.4 and 86.6 mg GAE 100 g -1 FW, respectively, the TP values of these accessions in our study were detected as 76.4, 58.9 and 73.4 mg of GAE 100 g -1 of FW, respectively, showing a decrease. While AOA values of 'Divrekkara' (TR1101), 'Sarılop' (TR1029) and 'Sarı Zeybek' (TR1098) accessions were 335, 178.06 and 144.04 µmol trolox 100 g -1 FW, respectively, AOA values belonging to the same accessions in the study by Konak et al [2015] were determined as 208, 70 and 99 µmol trolox 100 g -1 FW. When compared to the studies of the other researchers, TP and AOA values obtained from the same accessions vary in the range of 15 to 60 %.…”
Section: Source Of Fundingmentioning
confidence: 72%